Pengembangan Modul IPA Terintegrasi Al-Qur’an Berbasis Problem Based Learning (PBL) Dengan Strategi Scaffolding di MTsS Koto Tinggi-Pandai Sikek - Hijratul Husna; Najmiatul Fajar; Diyyan Marneli; M Haviz (Edusainstika: Jurnal Pembelajaran MIPA, 2022)
One of the this researcg is the lack of learning resources used, so the purpose of this research is to find out the result oh the validation and practical results oh the PBL based Al-Quran Integrated Science module og the Scaffolding strategy. The type og research conducted is research develompen or Reasearch and Development with a 4D model (Define, Design, Develop, dan Desseminate). The instruments used are validation sheets, student and educator practical sheets. The results obtained are for the validadot by 3 validators of the IPA module, they got a score of 92% (very valid). The results of the practivality of students are 81% (very practical) and 87% of teacher (very practical). It can be concluded that the developed science module is very valid and practical to use in science learning, especially the human digestive system material.Â